2018
DOI: 10.1007/s11213-018-9474-7
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Political Legitimacy and Conceptual Integration for Climate Change Adaptation Research within an Agricultural Bureaucracy: a Systemic Inquiry

Abstract: The value of using systems approaches, for situations framed as 'super wicked', is examined from the perspective of research managers and stakeholders in a state-based climate change adaptation (CCA) program (CliChAP) pre-2010 and polycentric drivers influencing the development of CCA research in Victoria, Australia are reflected on. Soft Systems Methodology (SSM) structured the inquiry beginning with a cultural analysis to generate a boundary critique of CCA research as a human activity system. We experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…In this research, we were able to introduce social science perspective as a gradual transition and find opportune moments to reflect on project design. However, along with others, we concluded that this needs to be built into sociotechnical design expectations (through agility, flexibility and emergence) to better manage projects and the learning and surprises they encounter [23,24,70]. Our finding was consistent with other sociotechnical innovation theory and knowledge developments that acknowledge the importance of agency or deliberation over change implications [27,71].…”
Section: Discussionsupporting
confidence: 88%
“…In this research, we were able to introduce social science perspective as a gradual transition and find opportune moments to reflect on project design. However, along with others, we concluded that this needs to be built into sociotechnical design expectations (through agility, flexibility and emergence) to better manage projects and the learning and surprises they encounter [23,24,70]. Our finding was consistent with other sociotechnical innovation theory and knowledge developments that acknowledge the importance of agency or deliberation over change implications [27,71].…”
Section: Discussionsupporting
confidence: 88%